Prototype Design of a Guidance and Counseling System Using the Human-Centered Design Method - Ranti Eka Putri (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
This study aims to design a prototype of a guidance and counseling system using the Human-Centered Design (HCD) method. This method is applied to ensure that the system developed focuses on the needs and experiences of users, particularly students and counselors in educational settings. The research process includes stages of user needs exploration, concept design, prototype development, and evaluation involving end users. The result is a web-based system prototype that is intuitive, facilitates counseling services efficiently, and enhances interactions between students and counselors. Preliminary evaluations indicate that the system effectively meets user needs and has the potential to improve the quality of guidance and counseling services. This prototype is expected to serve as an initial step in developing a more comprehensive system to support educational services.